2017
DOI: 10.1177/1559325817744450
|View full text |Cite
|
Sign up to set email alerts
|

Dual Effects of N,N-dimethylformamide on Cell Proliferation and Apoptosis in Breast Cancer

Abstract: N,N-dimethylformamide (DMF) has been widely used as an organic solvent in industries. DMF is a potential medication. However, the antitumorigenic role of DMF in breast cancer remains unclear. Here, we examined dose-dependent effects of DMF on proliferation and apoptosis in breast cancer MCF-7 and nontumorous MCF-12A cells. We found that DMF had a growth inhibitory effect in MCF-12A cells in a dose-dependent manner. By contrast, however, DMF had dual effects on cell proliferation and apoptosis in MCF-7 cells. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…In our research, the doses of DMF selected for the cell model were designed according to the cytotoxicity test results from our previous study (Jiang et al, 2020). Furthermore, the doses used in this study were consistent with those used in other previous in vitro studies, which showed a similar cell survival rate at the same doses of DMF (Rong et al, 2017; Zhang, Zhou, et al, 2017). We acknowledge that the level of DMF treatment used in our in vitro study was relatively higher than that in humans under occupational exposure.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our research, the doses of DMF selected for the cell model were designed according to the cytotoxicity test results from our previous study (Jiang et al, 2020). Furthermore, the doses used in this study were consistent with those used in other previous in vitro studies, which showed a similar cell survival rate at the same doses of DMF (Rong et al, 2017; Zhang, Zhou, et al, 2017). We acknowledge that the level of DMF treatment used in our in vitro study was relatively higher than that in humans under occupational exposure.…”
Section: Discussionsupporting
confidence: 89%
“…In addition to oxidative stress, apoptosis plays a pivotal role in DMF‐mediated hepatotoxicity. Some studies have indicated that DMF exposure can induce hepatic apoptosis through the activation of pro‐apoptotic genes and inhibition of anti‐apoptotic genes (Li & Wang, 2018; Rong et al, 2017; Zhang, Zhou, et al, 2017). However, the molecular mechanism of DMF‐induced hepatic apoptosis is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the use of DMF as a solvent to combine PCL with cellulose during the development of the composite, its complete evaporation is essential to in order not to affect the extrusion process and not to be retained in the polymeric network of the scaffolds, which causes cytotoxicity, since DMF is a very toxic organic solvent for cells [ 42 ]. The ATR–FTIR analysis ( Figure 2 ) demonstrated that DMF was fully removed from the composites since the band at 1673 cm −1 , which concerns the link vC=O, does not appear in the composites’ spectra.…”
Section: Discussionmentioning
confidence: 99%
“…For example, DMF has dual impacts on apoptosis and proliferation of breast cancer cells, depending on its concentration. 34 It induces a characteristic change of cells and suppresses tumorigenesis in human colon carcinoma cells. 35 DMF also inhibits cisplatin-related kidney injury by stimulating the Nrf2 pathway and repressing the NF-κB pathway.…”
Section: Discussionmentioning
confidence: 99%